Alteration of cardiac structure and function and its prognostic value in patients with Takayasu arteritis: a cardiac magnetic resonance study - Tang, Zehui; Wei, Chuangwei; Zhao, Wenjing; Liu, Dongting; Liu, Jiayi; Qin, Huai; Pan, Lili; Zhang, Nan; Wen, Zhaoying (Frontiers in Cardiovascular Medicine, 2024)
Purpose: To investigate the prevalence and characteristics of late gadolinium enhancement (LGE) by cardiac magnetic resonance (CMR) and its prognostic value in patients with Takayasu arteritis (TA).Sixty TA patients with a CMR examination were retrospectively included. All TA patients were divided into with LGE-positive andLGE-negative groups. Bi-ventricular function and location, distribution, and pattern of left ventricular (LV) LGE were evaluated in both LGE-positive and LGE-negative groups. Primary outcome was defined as a composite of cardiovascular death, hospitalization for heart failure, coronary artery revascularization, and stroke.Univariate and multivariate Cox proportional hazard regression analyses were used to evaluate the association between variables and primary outcomes.Results: Sixty consecutive TA patients were enrolled in this study. The mean age was 38.2 ± 13.8 years and 54 patients (54/60, 90.0%) were female. LGE-positive was observed in twenty-one (21/60, 35%) patients in the total patients with TA. LGE was predominantly distributed in the middle wall and subendocardial. The patchy and infarcted LGE patterns were the most common. Compared with the LGE-negative group, the LGE-positive group had reduced LV ejection fraction (P = 0.033), elevated LV end-diastolic volume index (P = 0.008), LV end-systolic volume index (P = 0.012), and LV mass (P = 0.008). During a median follow-up period of 1,892 days (interquartile range: 1,764-1,988 days), the primary outcomes occurred in thirteen patients. In the univariate analysis, LGE-positive (hazard ratio [HR] = 4.478, 95% confidence interval [CI]: 1.376-14.570; P = 0.013) were independently associated with the primary outcomes. However, LGE-positive did not retain its value as an independent predictor of primary outcomes in the multivariate analysis. Instead, LVMI (HR = 1.030, 95%CI: 1.013-1.048; P = 0.001) was the strongest independent predictor of primary outcomes in patients with TA. The Kaplan-Meier plot revealed that patients with LVMI ≥ 57.5g/m 2 have a worse prognosis.LGE-positive detected by CMR was observed in 35% of total TA patients with different distributions and patterns. LGE is associated with adverse LV remodeling and worsen cardiac function. However, LVMI rather than LGE can provide independent prognostic information in patients with TA.